2016
DOI: 10.1159/000444616
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Clinical Trial of Vibroplasty Couplers to Treat Mixed/Conductive Hearing Loss: First Results

Abstract: Objective: To evaluate the safety and effectiveness of round window (RW), oval window (OW), CliP and Bell couplers for use with an active middle ear implant. Methods: This is a multicenter, long-term, prospective trial with consecutive enrollment, involving 6 university hospitals in Germany. Bone conduction, air conduction, implant-aided warble-tone thresholds and Freiburger monosyllable word recognition scores were compared with unaided preimplantation results in 28 moderate-to-profound hearing-impaired patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 23 publications
2
26
0
3
Order By: Relevance
“…The present multicentre study aims to report, confirm and extend evidence of the long-term performance and safety of the VSB system in combination with vibroplasty couplers up to 36 months after VSB surgery. In addition, interim data of the same study collected up to 1 year after VSB [Zahnert et al, 2016] implantation should be substantiated by additional data provided in the present publication.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The present multicentre study aims to report, confirm and extend evidence of the long-term performance and safety of the VSB system in combination with vibroplasty couplers up to 36 months after VSB surgery. In addition, interim data of the same study collected up to 1 year after VSB [Zahnert et al, 2016] implantation should be substantiated by additional data provided in the present publication.…”
Section: Introductionmentioning
confidence: 80%
“…Subjects suffered from moderately severe (n = 9) over severe (n = 12) to profound (n = 3) hearing loss. Additional study inclusion and exclusion criteria are reported elsewhere [Zahnert et al, 2016]. The FMT was connected to the stapes (CliP coupler n = 3 or Bell coupler n = 5), the oval window (OW coupler n = 7) or the round window (RW coupler n = 9).…”
Section: Subjects and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main advantages of VSB in treating mixed or conductive hearing loss is that it can provide vibratory stimulation bypassing the external auditory canal and the damaged ossicular chain, often allowing the overclosure of airbone gap especially at 1-4 kHz. [10][11][12] Another advantage would be being able to be free of an ear level external device which can be a hindrance in radical cavities or auditory canals with chronic infections. 11) In patients with mixed or conductive hearing loss, the FMT of VSB may be connected to the round window, oval window, remnants of the ossicular chain depending on the condition of the middle ear either directly or using various couplers to improve the feasibility of surgical procedures and also the functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Systems that are in direct contact with the perilymphatic fluid via penetration of the membrane are also included in the definition [10]. Fixation can be achieved via coupling elements [13,14,33], additional prosthesis, and autologous or allogeneic materials [28].…”
Section: Active Middle Ear Implantsmentioning
confidence: 99%